Soy polysaccharide as a novel superdisintegrant in sildenafil citrate sublingual tablets: preparation, characterization, and in vivo evaluation - Hosny KM; Mosli HA; Hassan AH (Dove Medical Press, 2015)
Khaled Mohamed Hosny,1,2 Hisham Ahmed Mosli,3 Ali Habiballah Hassan4 1Department of Pharmaceutics and Industrial Pharmacy, Faculty of Pharmacy, King Abdulaziz University, Jeddah, Saudi Arabia; 2Department of Pharmaceutics and Industrial Pharmacy, Faculty of Pharmacy, Beni Suef University, Beni Suef, Egypt; 3Department of Urology, Faculty of Medicine, King Abdulaziz University, Jeddah, Saudi Arabia; 4Department of Orthodontics, Faculty of Dentistry, King Abdulaziz University, Jeddah, Saudi Arabia Abstract: Sildenafil citrate (SC), a drug used to treat erectile dysfunction, is available in tablet form but has three major problems. First, the drug displays inadequate aqueous solubility, which delays the onset of its action. Second, the drug undergoes extensive first-pass metabolism, resulting in a low (40%) bioavailability. Third, the gastrointestinal effects of SC include dyspepsia and a burning sensation. The aim of this research was to prepare SC as a sublingual tablet utilizing soy polysaccharide as novel superdisintegrant to mitigate the abovementioned problems. The solubility of SC in various hydrophilic carrier solutions was estimated in order to prepare the drug as a coprecipitate. Sublingual tablets were prepared and evaluated for hardness, friability, drug content, wetting time, water absorption ratio, in vitro dispersion time, dissolution rate, and stability study. The pharmacokinetic study of the tablets was carried out on healthy volunteers. The results indicated that the co-precipitation of SC with polyvinylpyrollidone K30 enhanced the solubility of SC by more than eight folds. The tablet contained 8% soy polysaccharide as a superdisintegrant and provided a wetting time of 25 seconds, and in vitro dispersion times of 55 seconds. The drug release was found to be 95.6%. The prepared SC sublingual tablet also exhibited a rapid onset of action, and its bioavailability was enhanced 1.68-fold compared with that of the marketed tablets. It can be concluded that SC sublingual tablet is a promising formulation that results in higher solubility, faster dispersion and onset of action, higher release rate, and higher systemic bioavailability. Keywords: bioavailability, erectile dysfunction, onset of action, polyvinylpyrrolidone, Emcosoy